The Issuance of PT Tambang Mas Sangihe’s Mining Operation Permit by the Ministry of Energy and Mineral Resources as an Act of Corruption - Clivio Rahardjo; Gabriel Maryo Lessil (Corruptio, 2025)
This paper analyzes the actions of the Minister of Energy and Mineral Resources (ESDM) in issuing a Mining Operation Permit to PT Tambang Mas Sangihe as a criminal act of corruption. Based on the Jakarta High Administrative Court (PTTUN) Decision No. 140/B/2022/PT.TUN.JKT, the permit was proven to violate several legal provisions and was subsequently revoked. The issuance of the permit without proper legal basis caused environmental damage and loss of natural resources, which form part of state finances. These actions indicate that the Minister of ESDM abused his authority to benefit a corporation, resulting in losses to state finances or the economy, as regulated in Article 3 of Law No. 31 of 1999 on the Eradication of Corruption. This study employs a normative legal research method using conceptual and case approaches, supported by primary and secondary legal materials.